Strengthening a Culture of Academic Integrity across a Faculty of Health Sciences & Wellness in the Face of COVID-19 - Miron, Jennie; Cameron, Tammy; Murphy, Wendy; Wojtalik, Sylwia; Tuba, Leanna (Canadian Perspectives on Academic Integrity, 2021)
The ongoing pandemic has presented unique challenges to our post-secondary learning communities, structures, pedagogies, and processes in Canada and around the world. An abrupt pivot to an all online learning environment created stressors that threatened the quality of educational offerings and the ability to cultivate and preserve cultures of academic integrity. The demands of the pandemic compelled members of the learning community to consider the many intersecting threats to teaching and learning efforts that went far beyond our abilities to incorporate technology across our educational settings. The psychosocial and emotional aspects of learning combined with the biological threat of COVID-19 created circumstances that jeopardized cultures of academic integrity and deeply affected all members of the learning community. In an effort to meet the many challenges associated with the dramatic and necessary changes to post-secondary education and continue to commit to the delivery of quality educational programming, the Faculty of Health Sciences & Wellness (FHSW) Academic Integrity Council at one college, stepped back to strategically plan efforts across the FHSW learning community, that would support academic integrity efforts during the continued pandemic. A framework developed by the co-chairs of the FHSW Academic Integrity Council served to ground the efforts of council members to create a plan to continue the building and strengthening of an academic integrity culture. This presentation will describe and discuss the framework, outline the strategic planning process adopted by the council, and outline plans for moving forward with future work across the FHSW in our efforts to strengthen academic integrity across our learning environments.